Revolutionizing energy infrastructure: Automated route planning for underground transmission lines in Phnom Penh - Saing, Kimlin; Goh, Hui Hwang; Zhang, Dongdong; Dai, Wei; Kurniawan, Tonni Agustiono; Goh, Kai Chen (elsevier, 2024)
The capacity of conventional overhead transmission lines (OTL) has been exceeded by the energy consumption of Cambodia’s flourishing cities. Underground transmission lines (UTL) provide a unique solution due to their technical and environmental advantages. However, engineers must contend with high UTL costs and the need for effective conduit cable installation. This study presents a solution that automates the shortest route method for determining the optimal path for routing UTL power supply cables between any two substations. Multiple algorithms are evaluated to identify the most effective solution to this design’s inherent shortest-path problem. Using Geographic Information System (GIS) data, potential UTL network routes in Phnom Penh, Cambodia can be investigated. The ultimate product is an automated route planning support tool that has the potential to revolutionize energy project planning by generating optimal routes for UTL. This will increase efficiency and lower costs, making UTL a more viable option for meeting the energy demands of modern infrastructure. This study contributes significantly to the field of energy infrastructure planning and has the potential to be replicated in cities around the world.